2011
DOI: 10.1161/circulationaha.110.987248
|View full text |Cite
|
Sign up to set email alerts
|

Striking In Vivo Phenotype of a Disease-Associated Human SCN5A Mutation Producing Minimal Changes in Vitro

Abstract: Background The D1275N SCN5A mutation has been associated with a range of unusual phenotypes including conduction disease and dilated cardiomyopathy (DCM) as well as atrial and ventricular tachyarrhythmias. However, when D1275N is studied in heterologous expression systems, most studies show near-normal sodium channel function. Thus, the relationship of the variant to the clinical phenotypes remains uncertain. Methods and results We identified D1275N in a patient with atrial flutter, atrial standstill, conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(99 citation statements)
references
References 48 publications
4
95
0
Order By: Relevance
“…As an example, although many studies have reported several varied phenotypes associating with a SCN5A p.D1275N missense mutation, for example, atrial standstill, dilated cardiomyopathy with conduction disease, atrial flutter/fibrillation, sick sinus syndrome, and ventricular dilation and dysfunction, the mutation does not induce marked Na v 1.5 dysfunction in vitro. However, when studied in genetically engineered mice, in vivo, the mutation generates extensive aberration of channel function, 21 underscoring that functional phenotypes may be influenced substantially by the experimental systems used.…”
Section: Gain-of-function Mutations In Na V 15 and The Clinical Phenmentioning
confidence: 99%
“…As an example, although many studies have reported several varied phenotypes associating with a SCN5A p.D1275N missense mutation, for example, atrial standstill, dilated cardiomyopathy with conduction disease, atrial flutter/fibrillation, sick sinus syndrome, and ventricular dilation and dysfunction, the mutation does not induce marked Na v 1.5 dysfunction in vitro. However, when studied in genetically engineered mice, in vivo, the mutation generates extensive aberration of channel function, 21 underscoring that functional phenotypes may be influenced substantially by the experimental systems used.…”
Section: Gain-of-function Mutations In Na V 15 and The Clinical Phenmentioning
confidence: 99%
“…11- 13 The reported electrophysiological properties of SCN5A-D1275N channels vary with experimental system; studies using heterologous expression systems showed no major differences between the mutant and wild-type (WT) channels, 14,15 whereas peak sodium current densities were reduced in SCN5A-D1275N knock-in mice than in WT ones. 16 The functional properties of SCN5A-D1275N channels in human cardiomyocytes (CMs) are currently unclear. Thus, the present study aimed to investigate the biophysical properties of SCN5A-D1275N channels using human-induced pluripotent stem cell-derived CMs (hiPSCCMs) generated from a patient with familial CCD who carried the SCN5A-D1275N mutation.…”
Section: Human-induced Pluripotent Stem Cell (Hipsc) Generation and Cmentioning
confidence: 99%
“…15 Recently, a study using a human SCN5A-D1275N knock-in mouse model reported that sodium channel protein levels and peak sodium current densities were lower in D1275N knock-in mice than in Controls. 16 Additionally, a study using a transgenic zebrafish model of SCN5A-D1275N demonstrated reduced heart rate, sinus pause, and AV block. 26 In order to assess the biophysical properties of SCN5A-D1275N channels in a human CM model, we generated hiPSCs from a patient carrying SCN5A-D1275N who had presented with SND and an AV block.…”
Section: D1275n Hipsc-cms Display Lower Sodium Channel Protein Expresmentioning
confidence: 99%
“…In this issue of the Journal, Hayano et al 8 report on the generation of iPSCs from the cells of a patient with SCN5A missense mutation D1275N, which did not result in major differences in the biophysical properties of the channel, compared with the wild-type channels in vitro. 9 The clinical manifestations of this mutation were sinus node dysfunction and atrioventricular block. The authors report that SCN5A-D1275N hiPSC-derived CMs showed reduced sodium channel protein expression and maximum sodium conductance.…”
Section: Cardiac Sodium Channel Disease Modeling With Ipscsmentioning
confidence: 99%